POLICY MODEL OF FINANCIAL RESPONSIBILITY AND MEASUREMENT OF BALI WOMEN PERFORMANCE IN SEKAA CINGKREMAN (FEASIBILITY STUDY OF PUBLIC SERVICES) - Sari Adnyani, Ni Ketut; Mandriani, Ni Nyoman; Putus Asrini, Ni Kadek (Ganesha Law Review, 2019)
This research is motivated by the problem of service management for members who are recruited as customers based on mutual agreement. In terms of implementation, this is commonly practiced by Balinese women to set aside a portion of their income to be saved (cingkreman). However, if it is identified by a mechanism based solely on agreement, sometimes if there is an dishonest administrator it will have an impact on the losses of its members who are cingkreman customers. The issue of accountability becomes urgent in measuring the financial responsibility of the employees; the management has not been able to measure performance in providing services to sekaa cingkreman members; Cingkreman savings collection which deposits are also based on agreement, in terms of recording still manual and not systematic indicates that financial management has not been organized on a number of occasions the influence of management of all cingkreman has not yet achieved optimal results. In general, this study aims to develop a model of financial accountability and measurement of the performance of Balinese women in sekaa cingkreman (feasibility studies of public services). The method used in this study is a type of research developing a public service policy model among members of the sekaa cingkreman consisting of Balinese women. The policy of financial accountability can be seen from the perspective of Transparency. The techniques of collecting data are observation, interviews and documentation studies, data analysis techniques using qualitative descriptive techniques. The results of this study are models of financial accountability policies that show public service by Balinese women who are members of the sekaa cingkreman.